THE CHINESE DRAGON IS THIRSTY FOR OIL AND GAS - SMIRNOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2004)
Twenty-five years ago China (despite its theoretically high annual economic growth rates of 7-8%) was teetering on the brink of hunger strikes and sociopolitical destabilization. The country was in the need of reform, the foundation for which was laid at the December (1978) Plenum of the CPC Central Committee. The reform policy is characterized by extremely careful and unhurried dismantling of the planned-distribution system and its gradual replacement with a market system. How-ever, it is based on the well-known pragmatic maxim coined by Deng Xiaoping: “It doesn’t matter what color the cat is as long as it catches mice.” This “cat,” the so-called “socialist market,” has taken root in the local soil and, by successfully “catching mice,” has led to the rapid development of the country’s economy. In this way, the attempt to create a market economic system by retaining the communist party’s monopoly on political power has been crowned with indisputable success. Today, the PRC is a country with a mixed economy, in which the share of the state sector in the GDP does not exceed 40%. There can be no doubt that long coexistence of two different systems has also given rise to significant losses. But the pluses of the strategy adopt-ed for reforming the economy still outweigh the minuses.